Cover Image, Volume 84, Issue 6. Issue 6 (June 2016) - Rigoldi, Federica; Gautieri, Alfonso; Dalle Vedove, Andrea; Lucarelli, Anna Paola; Vesentini, Simone; Parisini, Emilio
Abstract : The cover image, by Emilio Parisini et al., is based on the Article Crystal structure of the deglycating enzyme Amadoriase I in its free form and substrate‐bound complex, DOI:10.1002/prot.25015 .